2008
DOI: 10.1007/s00018-008-8249-1
|View full text |Cite
|
Sign up to set email alerts
|

Atomic model of human cystic fibrosis transmembrane conductance regulator: Membrane-spanning domains and coupling interfaces

Abstract: We describe herein an atomic model of the outward-facing three-dimensional structure of the membrane-spanning domains (MSDs) and nucleotide-binding domains (NBDs) of human cystic fibrosis transmembrane conductance regulator (CFTR), based on the experimental structure of the bacterial transporter Sav1866. This model, which is in agreement with previous experimental data, highlights the role of some residues located in the transmembrane passages and directly involved in substrate translocation and of some residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
233
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(253 citation statements)
references
References 81 publications
19
233
1
Order By: Relevance
“…One possibility is that each corrector interacts with a different structural feature of F508del-CFTR to stabilize their folding or reduce nonproductive folding intermediates. Because the folding defect of F508del involves multiple domain and interdomain interactions, multiple interaction sites may be necessary for optimal correction of the misfolded protein (33)(34)(35)(36)(37). Alternatively, rescue might be achieved indirectly through the modulation of folding chaperones or by suppressing ER-associated degradation (ERAD) quality control pathways that promote F508del-CFTR ubiquitylation and degradation.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that each corrector interacts with a different structural feature of F508del-CFTR to stabilize their folding or reduce nonproductive folding intermediates. Because the folding defect of F508del involves multiple domain and interdomain interactions, multiple interaction sites may be necessary for optimal correction of the misfolded protein (33)(34)(35)(36)(37). Alternatively, rescue might be achieved indirectly through the modulation of folding chaperones or by suppressing ER-associated degradation (ERAD) quality control pathways that promote F508del-CFTR ubiquitylation and degradation.…”
Section: Discussionmentioning
confidence: 99%
“…The outward facing models 14,[17][18][19][20][21][22][23] were based primarily on the Sav1866 structure as a template, 24 although recently the newly solved ABC transporter structure McjD 25 has been used to model this state. 26 Inward facing models were based either on the bacterial MsbA 27 or on the P-gp 28 structures.…”
Section: Introduction Cystic Fibrosis (Cf) Is a Lethal Inherited Dismentioning
confidence: 99%
“…Dysfunction of CFTR is directly associated with three devastating diseases: cystic fibrosis, polycystic kidney disease, and secretory diarrhea. Based on functional data and homology models, CFTR has been predicted to contain five functional domains: two membranespanning domains (MSDs), each including six transmembrane (TM) helices; two nucleotide binding domains (NBD1 and NBD2); and a unique regulatory (R) domain, which carries multiple protein kinase A (PKA) consensus phosphorylation sites and is unique to CFTR in the ABC superfamily (1)(2)(3)(4)(5)(6). Functional studies from multiple groups have suggested that TM6 plays an essential role and TM12 contributes less to anion conduction and permeation properties in the CFTR channel pore (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%